Study on Spatial-temporal Characteristics of Drought Duration and Intensity in Leizhou Peninsula in Recent 50 Years - DU Xiaoxia; TU Xinjun; XIE Yuting; WANG Tian (Renmin Zhujiang)
In the background of global warming,drought disasters occur frequently,bringing serious impacts on the natural ecosystem,human production and life and social & economic development.Therefore,it is of great significance to analyze and assess regional drought characteristics and study local drought mitigation and disaster reduction decisions and climate change.Based on the meteorological and hydrological data of 12 sites in Leizhou Peninsula from 1970 to 2019,this paper identifies and evaluates the drought events via standardised precipitation-evapotranspiration index (SPEI) and run theory,and analyzes the temporal and spatial variation characteristics of drought duration and intensity in Leizhou Peninsula in recent 50 years combined with curve fitting method,inverse distance weighted spatial interpolation,etc.The results show that:①The monthly SPEI index of the Leizhou Peninsula in recent 50 years showed a decreasing trend in fluctuation.On the time scale of the recent 50 years,it fluctuated with a period of about 10 years,which is related to the influence of ENSO.The SPEI is relatively high in cold event years,on the contrary,in warm event years,the SPEI is low and the drought is serious.②The greater the intensity of drought disaster in Leizhou Peninsula,the smaller the probability.③Due to regional difference,the spatial distribution of drought frequency,intensity and duration showed a gradually increase trend from the northeast to the southwest.④The regional difference of the occurrence frequency of drought of different grades showed that the frequency of moderate drought and above in the central and southern and northeastern regions of Leizhou Peninsula was higher than that in the central and northern regions.In addition,the drought in the southern part of Leizhou and Xuwen County was severe.⑤Droughts occur frequently in spring and winter.In spring and summer,the drought in the northeast and central-south part of the Leizhou Peninsula was more severe,the drought in autumn was more serious in the central-north part of the peninsula,and the drought in winter seriously affected the central-south part of the peninsula.